Technical comment on Sutin, A.R., Aschwanden, D., Stephan, Y & Terracciano, A. (2020). Five factor model personality traits and subjective cognitive failures. Personality and Individual Differences, 155, 109741. (September 2021) - Hall, Steven; Al-Talib, Nadhim
Abstract: This paper offers a technical commentary on the study of Sutin, Aschwanden, Stephan and Terracciano (2020), which used the Five Factor Model of personality to investigate subjective cognitive failures. The study seems to confirm earlier work in the area and also produces some surprising results. However, these results and conclusions may be spurious due to methodological issues, principally the apparent collinearity of both the independent and dependent variables.